Gold (Au): Metallic complexes applied against rheumatoid arthritis and cancer (Research, Society and Development, 2025)
The present article consists of a review study focused on the chemistry of gold (Au), especially gold (Au) metal complexes, covering the different possible oxidation states (gold(0), gold(I), gold(II) and gold(III)) and their applications as active ingredients of medicines, especially in the fight against rheumatoid arthritis (RA) and cancer. Gold (Au) is an element of the copper group (group 11) and has been considered one of the candidates for the replacement of the platinic coordination center (Pt) in metal complexes that act biologically in a similar way to the already classic metal complex known as "cisplatin", (cis-diaminodichloroplatin(II), cis-Pt(NH3)2Cl2), as well as their respective analogous compounds and successors. The aim of this article is to discuss, through a bibliographic review, the aspects of the medicinal chemistry of gold compounds (Au) and their mechanism of action in biological media, aiming at their use against different diseases, such as rheumatoid arthritis (RA) and various manifestations of cancer. The renowned drug Auranofin, its current context and the new attempts at pharmacological application of this renowned product are also discussed. Finally, future perspectives are presented for the applications of gold (Au) complexes both in the action as a drug against RA and in relation to its "anticancer action", either alone or as an adjuvant compound of platinic complexes.